Evolution of sex-determination in dioecious plants: from active Y to X/A balance? - Kazama, Y; Kobayashi, T; Filatov, DA (Wiley, 2023)
Sex chromosomes in plants have been known for a century, but only recently have we begun to understand the mechanisms behind sex determination in dioecious plants. Here, we discuss evolution of sex determination, focusing on Silene latifolia, where evolution of separate sexes is consistent with the classic “two mutations” model—a loss of function male sterility mutation and a gain of function gynoecium suppression mutation, which turned an ancestral hermaphroditic population into separate males and females. Interestingly, the gynoecium suppression function in S. latifolia evolved via loss of function in at least two sex-linked genes and works via gene dosage balance between sex-linked, and autosomal genes. This system resembles X/A-ratio-based sex determination systems in Drosophila and Rumex, and could represent a steppingstone in the evolution of X/A-ratio-based sex determination from an active Y system.